EasyCritics: I. Efficient detection of strongly lensing galaxy groups and clusters in wide-field surveys - Stapelberg, Sebastian; Carrasco, Mauricio; Maturi, Matteo (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We present EasyCritics, an algorithm to detect strongly lensing groups and clusters in wide-field surveys without relying on a direct recognition of
Advance access publication 2018 October 13
Gesehen am 19.08.2020